Analysis of postoperative morbidity and mortality following surgery for gastric cancer. Surgeon volume as the most significant prognostic factor - Maciej Ciesielski; Wiesław J. Kruszewski; Jakub Walczak; Mariusz Szajewski; Jarosław Szefel; Jacek Wydra; Tomasz Buczek; Maksymilian Czerepko (Gastroenterology Review)
Introduction : Surgical resection is the only potentially curative modality for gastric cancer and it is associated with substantial morbidity and mortality. Aim: To determine risk factors for postoperative morbidity and mortality following major surgery for gastric cancer. Material and methods : Between 1.08.2006 and 30.11.2014 in the Department of Oncological Surgery of Gdynia Oncology Centre 162 patients underwent gastric resection for adenocarcinoma. All procedures were performed by 13 surgeons. Five of them performed at least two gastrectomies per year (n = 106). The remaining 56 resections were done by eight surgeons with annual volume lower than two. Perioperative mortality was defined as every in-hospital death and death within 30 days after surgery. Causes of perioperative deaths were the matter of in-depth analysis. Results: Overall morbidity was 23.5%, including 4.3% rate of proximal anastomosis leak. Mortality rate was 4.3%. Morbidity and mortality were not dependent on: age, gender, body mass index, tumour location, extent of surgery, splenectomy performance, or pTNM stage. The rates of morbidity (50% vs. 21.3%) and mortality (16.7% vs. 3.3%) were significantly higher in cases of tumour infiltration to adjacent organs (pT4b). Perioperative morbidity and mortality were 37.5% and 8.9% for surgeons performing less than two gastrectomies per year and 16% and 0.9% for surgeons performing more than two resections annually. The differences were statistically significant (p = 0.002, p = 0.003). Conclusions : Annual surgeon case load and adjacent organ infiltration (pT4b) were significant risk factors for morbidity and mortality following major surgery for gastric cancer. The most common complications leading to perioperative death were cardiac failure and proximal anastomosis leak.